Woman Leadership In Management: Systematic Literature Review - Darmawani, Desi; Herachwati, Nuri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Research on women's leadership in management has shown significant interest for over the past sixty years. These studies delve into various aspects of women's leadership, perceptions of women as leaders, the suitability of women and men in leadership positions, and the barriers faced by women in holding leadership roles. Although more prevalent in developed countries and industries with a higher percentage of women in leadership positions, interest in women's leadership is steadily growing. This research provides crucial insights into understanding the barriers and experiences faced by women in leadership roles, with the aim of reducing gender gaps in leadership.